use implicit differentiation to find the 2nd derivative:

x^4+y^4=1

(pls do step by step, also when u solve for 1st deriv, you're to plug that answer for dy/dx when finding 2nd derivative)

1 answer

Sure! Let's start by implicitly differentiating both sides of the given equation with respect to x.

Given: x^4 + y^4 = 1

1. Implicitly differentiate both sides with respect to x
d/dx (x^4) + d/dx (y^4) = d/dx (1)

2. Apply the power rule
4x^3 + 4y^3 * dy/dx = 0
since, d/dx (y^4) = 4y^3 * dy/dx (chain rule)

3. Solve for dy/dx
4y^3 * dy/dx = -4x^3
dy/dx = -4x^3 / 4y^3
dy/dx = -x^3 / y^3

Now, we have found the first derivative. Next, we will find the second derivative by differentiating dy/dx with respect to x again.

dy/dx = -x^3/y^3

4. Differentiate both sides with respect to x
d^2y/dx^2 = d/dx (-x^3/y^3).

5. Apply the quotient rule
d^2y/dx^2 = (y^3 * d/dx(-x^3) - (-x^3) * d/dx (y^3)) / (y^3)^2

6. Apply the chain rule
d^2y/dx^2 = (y^3 * (-3x^2) - (-x^3) * (3y^2 * dy/dx)) / (y^6)

Recall that we found dy/dx earlier:
dy/dx = -x^3 / y^3

7. Substitute this back into the expression for d^2y/dx^2
d^2y/dx^2 = (y^3 * (-3x^2) - (-x^3) * (3y^2 * (-x^3 / y^3))) / (y^6)

8. Simplify the expression
d^2y/dx^2 = (-3x^2y^3 + 3x^6) / y^6

So, the second derivative is:
d^2y/dx^2 = (-3x^2y^3 + 3x^6) / y^6
Similar Questions
  1. use implicit differentiation to find the 2nd derivative:x^2-y^2=1 (pls do step by step, also when u solve for 1st deriv, you're
    1. answers icon 1 answer
  2. Find the equation of the tangent to 3x^2 +4y^2 =7 at P(1, 1).(pls provide step by step, use implicit differentiation when
    1. answers icon 1 answer
  3. Given y^4 -x^4=16 find and simplify d2y/dx2 using implicit differentiation.I got the first derivative which was x^3/y^3 and no
    1. answers icon 1 answer
  4. Step 1: 4x + 5 < 6x + 1 (Given)Step 2: −2x + 5 < 1 (Subtraction) Step 3: −2x < 6 (Addition) Step 4: x > −3 (Division) Mia
    1. answers icon 1 answer
more similar questions